Kebebasan beragama: gambaran Malaysia - Jalil, Faridah; Halim, Rohizan (Dewan Bahasa dan Pustaka, 2014)
This article will be discussing previous literature on the status of religious freedom concerning the right to change religion enshrined in the Malaysian Constitution.Our aim is to understand the flow of the various opinions on the issue of religious freedom in Malaysia.From the discussions, hopefully we will be able to form an appropriate understanding for Malaysian community with regard to freedom to change religion in the spirit of the Federal Constitution.